Missed Opportunities for Growth in the Posttraumatic Helping Environment: The Role of Spirituality - Wilmshurst, Kaitlin (Religions, 2022)
This paper focuses on social work’s understanding of how posttraumatic counselling may help or hinder recovery from trauma. A qualitative case study was conducted using an autobiographic memoir that provides an in-depth personal narrative of one woman’s experience of trauma, posttraumatic stress disorder, the posttraumatic helping environment, and healing journey. Inductive thematic analysis uncovered themes that align with the existing literature. Novel or understudied aspects for consideration also emerged, including the importance of psychoeducation, behavioural activation, and secondary factors related to the posttraumatic environment that impede healing. The analysis highlighted missed opportunities to clinically address issues of identity and meaning in a spiritually sensitive manner. Although the narrator made it clear to helping professionals that she was struggling with religious beliefs and was in spiritual crisis, helping professionals seemed to eschew exploration of these concerns. Implications for clinical social work practice and future research are discussed.